Analisa Perpindahan Panas dan Pengembunan pada Pengembunan Uap Cair dengan Pengembunan Parsial Bertingkat - Setyawan, Martomo (Universitas Ahmad Dahlan, 2015)
Production of charcoal as an alternative fuel have been growth as the solution of the national problem about decreasing energy source from petroleum. Production of charcoal has a useful side product in the form of liquid smoke. The liquid smoke can be used as food preservative in the high grade of liquid smoke and the low grade liquid smoke can be used as wood preservative form termite. The conventional process on production liquid smoke it was using redistillation the raw liquid smoke from direct condensation. This process was consumed lot of energy. Liquid smoke consist of some components which had different boiling point.The aim of this research was to study the influence in using different combination of vertical condensor at the condensation of liquid smoke process fro the making coconut shell charcoal. This research was done by make some coconut shell charcoal and the smoke which was formed was flown passed some condensors.The result of this research shown that condensation of liquid smoke in the vertical condenser occured a contactÂ between condensation down flow and the vapour. The temperature ofÂ the condensation taking point can be adjust by adjusting heat transfer area of the vertical condenser. The tar can be taken at the temperature above 100 0C. The colour of the liquid smoke was lighter with the lower temperature.